Research and Development on Animal Feed in Malaysia - Zahari, M Wan; Wong, H K (Indonesian Animal Sciences Society, 2009)
The growth of the non-ruminant sector to selfâsufficiency in meat and eggs has been matched by massive importation of feed. Thus, a major thrust to reduce the burden of feed imports is to increase the use of indigenous feed resources and intensify research to look for alternatives and substitutes. Over the past 3 decades, local researchers have reported on the availability nutritive content, optimal inclusion levels and treatment methods to enhance nutrient value of many locally available feed ingredients in practical poultry rations. The list includes evaluation and utilization of feed rice, palm kernel cake (PKC), broken rice, bran, sorghum, cassava, sago, fishmeal and commercial grain corn production; but the goal of import substitution and self- sufficiency is still unfulfilled. Although PKC, feed rice, local maize and specialty fats has potential to be viable energy feed sources and local fish meal is a promising protein feed source, more large scale Research and Development (R & D) is needed. In the ruminant sub-sector, emphasis is towards maximizing use of locally available agro-industrial byproducts and crop residues for the production of cost-effective feeds. The utilization of local feed resources is highly dependent on the supply of agro- industrial byproducts or crop residues from the oil palm and rice industries. In order to encourage a sustainable ruminant industry in Malaysia, local feed production has to be maximized and strengthened. Current emphasis is towards the development of practical and low-cost feeds for various classes of livestock species, particularly by utilizing local forages, tree fodders, crop residues and agro-industrial byproducts. This paper highlights the research and development on animal feed in Malaysia over the last three decades and discusses various aspects of livestock feeding. Â Key words: Feed, resources, indigenous, ruminant, non-ruminant